2022
DOI: 10.3389/fgene.2022.1004392
|View full text |Cite
|
Sign up to set email alerts
|

Genetically predicted tea intake increases the risk of osteoarthritis: A Mendelian randomization study

Abstract: Background: This study aimed to clarify the relationship between tea consumption and osteoarthritis (OA).Methods: Common single-nucleotide polymorphisms (SNPs) from the Open Genome-wide Association Studies database were obtained. Summary statistics on OA were retrieved from the second dataset that enrolled 50,508 participants (10,083 OA cases) of European ancestry. The causal association between tea intake and OA was tested using two-sample Mendelian randomization (MR) analysis.Results: Tea consumption has adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(49 reference statements)
1
0
0
Order By: Relevance
“…For the effect of coffee and tea intake on OA, our findings are consistent with previous similar univariate MR studies ( 10 , 11 ). For alcohol intake, a previous MR study found the frequency of alcohol intake to be a risk factor for hip and knee osteoarthritis ( 12 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For the effect of coffee and tea intake on OA, our findings are consistent with previous similar univariate MR studies ( 10 , 11 ). For alcohol intake, a previous MR study found the frequency of alcohol intake to be a risk factor for hip and knee osteoarthritis ( 12 ).…”
Section: Discussionsupporting
confidence: 92%
“…In this situation, Mendelian randomization (MR) analyses provide us with a suitable method to investigate the causal relationship between specific dietary intake and osteoarthritis, utilizing single nucleotide polymorphisms as instrumental variables (IVs), which are less susceptible to confounding factors because gametes are randomly assigned during gamete formation and are independent of environmental factors (9). Previous MR analyses have explored the causal effects of coffee consumption, tea, and alcohol intake on osteoarthritis of the hip and knee (10)(11)(12). However, these studies did not classify drinks in detail and only analyzed the effects of drinks on the most common types of osteoarthritis of the hip and knee.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive tea consumption, which contains flavan-3-ols, may have a negative impact on OA risk. This is corroborated by a two-sample Mendelian randomization analysis, 34 which examined common single-nucleotide polymorphisms from 50 508 samples (including 10 083 OA cases) from the Genome-wide Association Studies database; this prior study found that excessive daily intake of tea (the main source of flavan-3-ol monomers) may result in an increased OA risk, with an inverse-variance weighted OR of 1.19 (95% CI: 1.08–1.30). Consuming large amounts of flavan-3-ols involves drinking a substantial quantity of tea, which may result in harmful substances entering the human body.…”
Section: Discussionmentioning
confidence: 58%
“…Single nucleotide polymorphism (SNP) was defined as the instrumental variable (IV). Exposure and outcome data were obtained from a publicly available Genome-Wide Association Study (GWAS) database ( https://gwas.mrcieu.ac.uk/) [ 24 ]. Subsequently, the significant pathway Pyruvate metabolism (ID: ebi-a-GCST90092942) and the disease BC (ID: ebi-a-GCST007236) were chosen for the MR analysis.…”
Section: Methodsmentioning
confidence: 99%